(untitled) (Global Journal of Management and Business Research, 2013)
In this paper, we’ll try to study the impact of governance indicators and macroeconomic variables on the attractiveness of foreign direct investment in 20 developed and developing countries over the period 1998-2011 using fixed effects panel regressions. Our results generally indicate that only two indicators of governance namely, political stability and regulatory quality have a significant impact on FDI inflows. This indicates, for our overall sample, that foreign investors are interested in political stability and regulatory quality in their choice of investment abroad.